Implementasi Web Application Firewall Untuk Meningkatkan Keamanan Aplikasi Owasp Juice Shop Terhadap Serangan Sql Injection, Cross-Site Scripting (Xss), Insecure Direct Object Reference (Idor), Dan Information Disclosure - Dian Suryo Aji; Dwi Safiroh Utsalina (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
The increasing use of web applications in various sectors has made security a major concern due to the high risk of attacks targeting the application layer. This study aims to analyze the effectiveness of the F5 Web Application Firewall (F5 WAF) in mitigating vulnerabilities in the OWASP Juice Shop application. Testing was conducted using 10 attack scenarios including SQL Injection, Cross-Site Scripting (XSS), Insecure Direct Object Reference (IDOR), and Information Disclosure before and after F5 WAF implementation. The test results showed that all tested attack scenarios were successfully mitigated after F5 WAF implementation. These findings indicate that the F5 WAF is able to provide effective protection against various vulnerabilities at the application layer and improve the security of web applications in the test environment used.